2019
DOI: 10.1029/2019gl082824
|View full text |Cite
|
Sign up to set email alerts
|

Directed Network of Substorms Using SuperMAG Ground‐Based Magnetometer Data

Abstract: We quantify the spatiotemporal evolution of the substorm ionospheric current system utilizing the SuperMAG 100+ magnetometers. We construct dynamical directed networks from this data for the first time. If the canonical cross‐correlation between vector magnetic field perturbations observed at two magnetometer stations exceeds a threshold, they form a network connection. The time lag at which canonical cross‐correlation is maximal determines the direction of propagation or expansion of the structure captured by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…The network has been constructed by identifying connections using the canonical cross-correlation (CCC) lag at which the CCC between each pair of magnetometers is at its peak so that each connection has an associated lag, τ c . The magnitude of the lag ∣ τ c ∣ indicates whether connections within a given community are formed rapidly (zero CCC lag i.e., τ c = 0 (gray)) or whether they are associated with propagation and/or expansion (non-zero CCC lags from 1 to 15 min (blue-red)) 27 , see “Methods,” “Calculating the direct network.”…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The network has been constructed by identifying connections using the canonical cross-correlation (CCC) lag at which the CCC between each pair of magnetometers is at its peak so that each connection has an associated lag, τ c . The magnitude of the lag ∣ τ c ∣ indicates whether connections within a given community are formed rapidly (zero CCC lag i.e., τ c = 0 (gray)) or whether they are associated with propagation and/or expansion (non-zero CCC lags from 1 to 15 min (blue-red)) 27 , see “Methods,” “Calculating the direct network.”…”
Section: Resultsmentioning
confidence: 99%
“…The details of the underpinning methodology for forming the raw network are detailed in refs. 27 , 34 and we summarize it here. The magnetometers are the nodes of the network and a pair of nodes are connected (have an edge between them) if the CCC 46 of their vector magnetic field perturbation time series exceeds a station and event-specific threshold.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, using data from the WIC and SI12 instruments on IMAGE, Walach et al (2017) found that the brightening of the electron auroral oval expanded toward the dawn and dusk sectors 10–40 minutes after substorm onset, during the substorm expansion phase, covering 12 hours of MLT. In contrast, by applying directed network analysis to ground magnetometer data, Orr et al (2019) found that magnetic perturbations associated with substorm activity and loosely linked to the auroral bulge expanded westward toward the dusk MLT sectors after substorm onset before expanding dawnward at a later time. We found that the average rate of expansion of the region of contracting OCB toward the dawn and dusk directions was |0.2| and |0.3| MLT/minutes, respectively, corresponding to approximately 1.1 km/s at 65° latitude, in agreement with these earlier studies of the expansion of the auroral brightness and westward and eastward moving surges.…”
Section: Discussionmentioning
confidence: 99%